Acupuncture in the treatment of chemotherapy-induced peripheral neuropathy: a meta-analysis and data mining - Li, Limeng; Huang, Yingxue; An, Chengfei; Jing, Ning; Xu, Chuhan; Wang, Xiaoyu; Li, Huanan; Tan, Tao (Frontiers in Neurology, 2024)
Background The efficacy and acupoint selection of acupuncture in treating chemotherapy-induced peripheral neuropathy (CIPN) remain controversial. This study aims to explore the specific efficacy and acupoint selection of acupuncture in treating CIPN through a meta-analysis and data mining. Methods Searching for clinical trials on acupuncture treatment for CIPN in 8 databases, evaluating its efficacy and safety through a meta-analysis, and exploring its acupoint selection through data mining. Results The meta-analysis included 21 studies and 2,121 patients, showing that compared with the control group, the acupuncture group could significantly improve neuropathic pain intensity (SMD = −0.66, 95% CI [−1.07, −0.25], p = 0.002), significantly reduce the NCI-CTCAE (MD = −0.29, 95%CI [−0.50, −0.08], p < 0.01), significantly reduce the FACT-NXT score (MD = 2.09, 95% CI [0.73,3.45], p < 0.05), significantly increase the motor conduction velocities (MCV) of median nerve (MD = 2.38, 95% CI [2.10, 2.67], p < 0.001), the sensory conduction velocities (SCV) of the median nerve (MD = 0.56, 95 %CI [−1.45, 2.57], p = 0.58), the SCV of the tibial nerve (MD = 1.78, 95% CI [0.50, 3.05], p < 0.01), and the SCV of sural nerves (MD = 4.60, 95% CI [0.17, 9.02], p < 0.05), as well as improving the quality of life score (MD =7.35, 95% CI [1.53, 13.18], p = 0.01). Data mining showed that the core acupoints for acupuncture treatment of CIPN were LI4, ST36, LI11, LR3, and SP6. Conclusion Acupuncture can improve the neuropathic pain intensity, the intensity of the CIPN, MCV of the median nerve, SCV of the tibial nerve and peroneal nerve, quality of life, and has good safety in CIPN patients. LI4 (Hegu), ST36 (Zusanli), LI11 (Quchi), LR3 (Taichong), and SP6 (Sanyinjiao) are the core acupuncture points for treating CIPN, and this protocol has the potential to become a supplementary treatment for CIPN. Systematic review registration https://www.crd.york.ac.uk/prospero, identifier CRD42024551137.